Deletion of the Pyrophosphate Generating Enzyme ENPP1 Rescues Craniofacial Abnormalities in the TNAP−/− Mouse Model of Hypophosphatasia and Reveals FGF23 as a Marker of Phenotype Severity - Nam, Hwa Kyung; Emmanouil, Emmanouil; Hatch, Nan E. (Frontiers in Dental Medicine, 2022)
Hypophosphatasia is a rare heritable metabolic disorder caused by deficient Tissue Nonspecific Alkaline Phosphatase (TNAP) enzyme activity. A principal function of TNAP is to hydrolyze the tissue mineralization inhibitor pyrophosphate. ENPP1 (Ectonucleotide Pyrophosphatase/Phosphodiesterase 1) is a primary enzymatic generator of pyrophosphate and prior results showed that elimination of ENPP1 rescued bone hypomineralization of skull, vertebral and long bones to different extents in TNAP null mice. Current TNAP enzyme replacement therapy alleviates skeletal, motor and cognitive defects but does not eliminate craniosynostosis in pediatric hypophosphatasia patients. To further understand mechanisms underlying craniosynostosis development in hypophosphatasia, here we sought to determine if craniofacial abnormalities including craniosynostosis and skull shape defects would be alleviated in TNAP null mice by genetic ablation of ENPP1. Results show that homozygous deletion of ENPP1 significantly diminishes the incidence of craniosynostosis and that skull shape abnormalities are rescued by hemi- or homozygous deletion of ENPP1 in TNAP null mice. Skull and long bone hypomineralization were also alleviated in TNAP-/-/ENPP1-/- compared to TNAP-/-/ENPP1+/+ mice, though loss of ENPP1 in combination with TNAP has differential effects than loss of only TNAP on long bone trabeculae. Investigation of a relatively large cohort of mice revealed that the skeletal phenotypes of TNAP null mice were markedly variable. Because FGF23 circulating levels are known to be increased in ENPP1 null mice and because FGF23 influences bone, we measured serum intact FGF23 levels in the TNAP null mice and found that a subset of TNAP-/-/ENPP1+/+ mice exhibited markedly high serum FGF23. Serum FGF23 levels also correlated to mouse body measurements, the incidence of craniosynostosis, skull shape abnormalities and skull bone density and volume fraction. Together, our results demonstrate that balanced expression of TNAP and ENPP1 enzymes are essential for microstructure and mineralization of both skull and long bones and for preventing craniosynostosis. The results also show that FGF23 rises in the TNAP-/- model of murine lethal hypophosphatasia. Future studies are required to determine if the rise in FGF23 is a cause, consequence, or marker of disease phenotype severity.